2002
DOI: 10.1209/epl/i2002-00309-6
|View full text |Cite
|
Sign up to set email alerts
|

Stress response function of a two-dimensional ordered packing of frictional beads

Abstract: Abstract. -We study the stress profile of an ordered two-dimensional packing of beads in response to the application of a vertical overload localized at its top surface. Disorder is introduced through the Coulombic friction between the grains which gives some indeterminacy and allows the choice of one constrained random number per grain in the calculation of the contact forces. The so-called 'multi-agent' technique we use, lets us deal with systems as large as 1000×1000 grains. We show that the average respons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 28 publications
4
21
0
Order By: Relevance
“…This crosses over to an anisotropic response function of the double-peak variety further from the source. This double-peak feature is suitably captured by the modified Convection-Wave equation; peak widths scaling linearly with distance, rather than the diffusive form of this equation [9]. These results are consistent with a generalisation from 2D to 3D anisotropic elasticity theories [32].…”
Section: Discussionsupporting
confidence: 77%
“…This crosses over to an anisotropic response function of the double-peak variety further from the source. This double-peak feature is suitably captured by the modified Convection-Wave equation; peak widths scaling linearly with distance, rather than the diffusive form of this equation [9]. These results are consistent with a generalisation from 2D to 3D anisotropic elasticity theories [32].…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies of the static load transfer path in 2D granular systems showed that ordered granular arrays allow the load to be transmitted primarily along lattice vectors [7][8][9][10], while disordered particle arrangements result in complicated force chain networks [7,[10][11][12][13]. The role of force chains in the dynamic load transfer within disordered granular systems has also been studied [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been suggested that irregularities in particle surface profiles could lead to deviations from Hertzian behavior and reorganization of particles between successive experiments * andreal@caltech.edu † daraio@caltech.edu ‡ amnaya@illinois.edu § geubelle@illinois.edu [23]. Other sources of disorder stem from the redundancy in particle contacts in densely packed arrays and the presence of friction [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations